2020
DOI: 10.1002/smll.202003557
|View full text |Cite
|
Sign up to set email alerts
|

Tin Nanodots Derived From Sn2+/Graphene Quantum Dot Complex as Pillars into Graphene Blocks for Ultrafast and Ultrastable Sodium‐Ion Storage

Abstract: Tin (Sn) is considered to be an ideal candidate for the anode of sodium ion batteries. However, the design of Sn-based electrodes with maintained longterm stability still remains challenging due to their huge volume expansion (≈420%) and easy pulverization during cycling. Herein, a facile and versatile strategy for the synthesis of nitrogen-doped graphene quantum dot (GQD) edge-anchored Sn nanodots as the pillars into reduced graphene oxide blocks (NGQD/Sn-NG) for ultrafast and ultrastable sodium-ion storage i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…Meanwhile, the characteristic peak concentrated at ~1720 cm À 1 in the FTIR results for COF-GQDs can be attributed to the C=O functional groups for GQDs with carboxyl groups. [40] Furthermore, the chemical composition of COF-GQDs was evaluated by XPS. The survey spectrum of COF-GQDs is displayed in Figure 1c There are two peaks at the location of 399.5 and 401.9 eV in the N 1s spectrum (Figure 1e), corresponding to the aromatic nitrogen and pyrrolic nitrogen.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the characteristic peak concentrated at ~1720 cm À 1 in the FTIR results for COF-GQDs can be attributed to the C=O functional groups for GQDs with carboxyl groups. [40] Furthermore, the chemical composition of COF-GQDs was evaluated by XPS. The survey spectrum of COF-GQDs is displayed in Figure 1c There are two peaks at the location of 399.5 and 401.9 eV in the N 1s spectrum (Figure 1e), corresponding to the aromatic nitrogen and pyrrolic nitrogen.…”
Section: Resultsmentioning
confidence: 99%
“…It is also expected that the GQD introduction can decrease the electrochemical impedance and thus facilitates the Li + ion transportation kinetics, which has also been witnessed in previous references. [40] To explore on the lithium-storage motivation for the COF-GQDs and original COF electrodes, the lithium-reaction kinetics behavior was investigated by CV measurements under scan rates from 0.2 to 0.8 mV s À 1 (Figure 4a). Similar shapes of the CV curves were detected under separate scan rates, demonstrating the superior reversibility of the COF-GQDs electrode.…”
Section: Chemistry-a European Journalmentioning
confidence: 99%
“…The reason for the increase in fluorescence intensity may be that the transfer process of photogenerated electrons is inhibited. 53 Specifically, the lone pair of electrons can be transferred spontaneously under ultraviolet light for a single TQD, thereby quenching the fluorescence of the TQD skeleton. After combining with Sn 2+ , the lone pair of electrons of the terminal groups, such as hydroxyl groups, can quickly capture Sn 2+ through the potential difference between O and Sn to inhibit the photogenerated electron transfer process and excite fluorescence.…”
Section: Resultsmentioning
confidence: 99%
“…Tin (Sn 2+ ) with excellent conductivity and high activity is an ideal candidate in catalysis [46][47][48][49] and ion storage. [50][51][52] Liu et al 53 have combined graphene quantum dots with Sn through electrostatic interactions as pillars into reduced graphene oxide blocks for Na-ion storage. It has been shown that quantum dots can be successfully combined with Sn 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…reported the synthesis of a N‐doped GQD edge‐anchored Sn nanodots pillared graphene block composite (NGQD/Sn‐NG). [ 115 ] The negatively charged ‐COOH groups on the edge of GQDs acted like “octopus” tentacles to capture Sn 2+ , with the modified GQDs assembled with graphene oxide (GO) by electrostatic forces to form GQDs/Sn 2+ composite pillared GO blocks (Figure 19b). After reduction with NH 3 , Sn nanodots (2–5 nm) were pinned on edges of the GQDs through SnOC or SnNC bonds.…”
Section: Applications Of Cds In Energy Storagementioning
confidence: 99%